Characterisation and intracellular labelling of mesenchymal stromal cells derived from synovial fluid of horses and sheep. (April 2017) - Burk, J.; Glauche, S.M.; Brehm, W.; Crovace, A.; Francioso, E.; Hillmann, A.; Schubert, S.; Lacitignola, L.
Highlights: Mesenchymal stromal cells (MSCs) from synovial fluid are a minimally invasive source of cells for potential joint therapy. Equine and ovine synovial fluid-derived MSCs exhibit similar but not identical characteristics. Synovial fluid-derived MSCs from sheep exhibit better chondrogenic differentiation potential than those from horses. Quantum dot intracellular labelling did not adversely affect cell quality and could be used for short-term cell tracking studies. The current data provide a basis for in vivo applications of synovial fluid-derived MSCs in horses and sheep. Abstract: Multipotent mesenchymal stromal cells (MSCs) derived from synovial fluid (SF) are considered to be a promising cell type for therapeutic applications in joint disease. However, despite their potential relevance for clinical and experimental studies, there is insufficient knowledge about SF-derived MSCs isolated from horses and sheep. In this study, cells were recovered from healthy SF and bone marrow (BM) of sheep, and from healthy and osteoarthritic SF of horses. Ovine SF-MSCs were used to assess the efficiency of intracellular labelling with quantum dots (QDs). Colony forming units, generation times, trilineage differentiation potential and expression of CD73, CD90 and CD105 at mRNA level were assessed. QD labelling was efficient, with >98% positive cells directly after labelling at 10 nmol/L and >95% positive cells directly after labelling at 2 nmol/L. The label decreased over 7 days of culture, with more persistence at the higher labelling concentration. No significant differences in proliferation were observed. All MSCs had trilineage differentiation potential, but adipogenesis was more distinct in equine samples and chondrogenesis was most pronounced in ovine SF-MSCs. CD73, CD90 and CD105 were expressed in equine and ovine MSCs.